2018
DOI: 10.1364/ome.8.003635
|View full text |Cite
|
Sign up to set email alerts
|

Tunable white light emission of a large area film-forming macromolecular complex with a high color rendering index

Abstract: The technological route of pre-polymerization and post-coordination was employed to obtain a rapid film-forming macromolecular complex emitting white light by simultaneously combining poly (styrene-co-glycidyl methacrylate) with three primary color complexes [r(R)/g(G)/b(B)]. The white light emission of the macromolecular complex was realized by tuning the ratios of the trichromatic complexes or altering excitation wavelengths. Upon excitation at 365 nm, macromolecular complex 5 with R:G:B = 1:10:1 exhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…In 2017, Nhan and his partners reported that structure with red phosphor SrO.3B2O3:Sm 2+ in the dual remote phosphor can enhance light output by 17% in comparison to the conventional phosphor configuration. Besides, in the stable concentration of red phosphor SrO.3B2O3:Sm 2+ , the structure can achieve 5% higher color rendering index (CRI) than the mixed phosphor WLEDs [22,23]. However, this study just showed the better results of CRI which is one of elements using to evaluate the color quality.…”
Section: Introductionmentioning
confidence: 70%
“…In 2017, Nhan and his partners reported that structure with red phosphor SrO.3B2O3:Sm 2+ in the dual remote phosphor can enhance light output by 17% in comparison to the conventional phosphor configuration. Besides, in the stable concentration of red phosphor SrO.3B2O3:Sm 2+ , the structure can achieve 5% higher color rendering index (CRI) than the mixed phosphor WLEDs [22,23]. However, this study just showed the better results of CRI which is one of elements using to evaluate the color quality.…”
Section: Introductionmentioning
confidence: 70%
“…In order to confirm the optical properties of phosphor compounding, the scattering coefficient μsca are calculated based on the Mie theory [25]. The following expressions demonstrate the connection among the three elements: the scattering coefficient (SC), the wavelength, and the size of MgCeAl11O19:Tb 3+ particles.…”
Section: Computation and Discussionmentioning
confidence: 99%
“…HfO 2 /SiO 2 DBR film, on the other hand, can lower the color deviation from 1758 K to 280 K at 5000 K CCT [7]. Finally, the micro-patterned is also effective by deducting about 441 K color deviation value at 5337 K CCT [8]. The effects of these mentioned methods in boosting spatial color homogeneity are profound and have been tested, however, the complexity in fabrication as well as the high manufacturing cost prevent them from being widely used.…”
Section: Introductionmentioning
confidence: 97%